Determinants of Islamic Business Coach's Role Success in The VUCA Era - Sholahuddin, Muhammad; Abdullah, Moha Asri; Barom, Mohd. Nizam (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study embarks on an explorative journey into the complex role of Islamic business coaches, particularly in the context of the VUCA (Volatility, Uncertainty, Complexity, Ambiguity) era. It aims to dissect and comprehend the various aspects that define their roles and responsibilities. The research encompasses an analysis of data collected from 150 Sharia-compliant business professionals, applying Exploratory Factor Analysis and reliability testing to uncover core dimensions of Islamic business coaching. These dimensions are identified as (1) Listener, emphasizing empathetic engagement; (2) Sound Board, enhancing problem-solving capabilities; (3) Counselor, providing ethical guidance; and (4) Spiritual Motivator, fostering leadership values rooted in Islamic principles. This study's innovative approach not only deepens the understanding of Islamic business coaching roles in the VUCA era but also extends its relevance to a broader audience, underscoring the universal appeal of ethical and spiritually informed business practices. By introducing a novel framework, this research advances academic knowledge and practical applications in Islamic business coaching, bridging cultural and religious divides and promoting a holistic approach that aligns with Islamic values and ethics, while being inclusive and applicable to a diverse global business community.